2021
DOI: 10.1007/s11739-021-02836-3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety of rituximab in rheumatic patients with previously resolved hepatitis B virus infection

Abstract: Conflicting results can be found in the literature on the frequency of hepatitis B virus (HBV) reactivation (HBVr) on rituximab (RTX) in rheumatic patients with previously resolved HBV (prHBV) infection. Here, we report the frequency of HBVr in a large historical cohort of caucasian rheumatic patients with prHBV receiving RTX. Registry data of rheumatic patients treated with RTX were retrospectively analysed. Demographic and clinical characteristics including evaluation of anti-HCV and HBV markers, annual HBV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…On the other hand, in an Italian study, seroconversion and positive HBV-DNA levels were recorded in 0% and 3%, respectively, in 33 patients with RA treated with rituximab 151. In another study, HBV reactivation was not seen in 44 RA, anti-HBcore-positive patients treated with rituximab 152. A recent study, examining 489 patients with resolved HBV, also showed that treatment with rituximab or abatacept were independent risk factors for HBsAg conversion (HR 87.76, 95% CI 11.50 to 669.73, p<0.001; HR 60.57, 95% CI 6.99 to 525.15, respectively) in patients with resolved HBV 153.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…On the other hand, in an Italian study, seroconversion and positive HBV-DNA levels were recorded in 0% and 3%, respectively, in 33 patients with RA treated with rituximab 151. In another study, HBV reactivation was not seen in 44 RA, anti-HBcore-positive patients treated with rituximab 152. A recent study, examining 489 patients with resolved HBV, also showed that treatment with rituximab or abatacept were independent risk factors for HBsAg conversion (HR 87.76, 95% CI 11.50 to 669.73, p<0.001; HR 60.57, 95% CI 6.99 to 525.15, respectively) in patients with resolved HBV 153.…”
Section: Resultsmentioning
confidence: 91%
“… 151 In another study, HBV reactivation was not seen in 44 RA, anti-HBcore-positive patients treated with rituximab. 152 A recent study, examining 489 patients with resolved HBV, also showed that treatment with rituximab or abatacept were independent risk factors for HBsAg conversion (HR 87.76, 95% CI 11.50 to 669.73, p<0.001; HR 60.57, 95% CI 6.99 to 525.15, respectively) in patients with resolved HBV. 153 Data on tsDMARDs are limited.…”
Section: Resultsmentioning
confidence: 94%